2021
DOI: 10.1089/vbz.2020.2765
|View full text |Cite
|
Sign up to set email alerts
|

Plague Exposure in Mammalian Wildlife Across the Western United States

Abstract: Plague is caused by a bacterial pathogen (Yersinia pestis) that can infect a wide range of mammal species, but its presence in wildlife is often underappreciated. Using a large-scale data set (n = 44,857) that details the extent of Y. pestis exposure in wildlife, we document exposure in 18 wildlife species, including coyotes (Canis latrans), bobcats (Lynx rufus), and black bears (Ursus americanus). Evidence of plague activity is widespread, with seropositive animals detected in every western state in the conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Across the US, reported seroprevalence in coyotes ranges from 0 to 73% in California, Utah, and Wyoming (Arjo et al 2003), 12% in California (Hoar et al 2003), 13% in South Dakota (Schuler et al 2021) and 28% in urban environments in Denver, Colorado (Malmlov et al 2014). Bevins et al (2021) reported 8.5% plague seroprevalence in New Mexico's coyotes, and 20.5% exposure rates to plague among all mammals monitored in New Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Across the US, reported seroprevalence in coyotes ranges from 0 to 73% in California, Utah, and Wyoming (Arjo et al 2003), 12% in California (Hoar et al 2003), 13% in South Dakota (Schuler et al 2021) and 28% in urban environments in Denver, Colorado (Malmlov et al 2014). Bevins et al (2021) reported 8.5% plague seroprevalence in New Mexico's coyotes, and 20.5% exposure rates to plague among all mammals monitored in New Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially at home in populations of small mammals, typically rodents, but even so, the range of infected species within a focus can be much wider than this and include predators such as coyotes, bobcats and black bears as seen in the Western United States [19]. Some foci, for example those found across the territories of the Russian Federation and former Soviet republics, are believed to be ancient [20] whilst others such as the island of Madagascar [12] or the Mid-West of America are more recent, being the product of communication and trade [19]. There is a risk of human plague wherever the presence of plague natural foci and human populations co-exist.…”
Section: The Location and Frequency Of Pp Outbreaksmentioning
confidence: 99%
“…In the case of large wild mammals, some studies have demonstrated relationships between oxidative stress markers and living environments both for individual populations and for the interspecific territory sharing [6,7]. Great interest nowadays is given to soil born-diseases [8,9], and, in wildlife, studies are mainly focused on soil pathogens which are of public health interest such as Francisella tularensis, Yersinia pestis, Bacillus anthracis, Coxiella burnetii, Avian influenza virus H5N1 [10], Swine flu H1N1 [11], Coronavirus [12], and different helminths [13] as they can negatively affect humans, livestock and domestic animals [14][15][16][17][18][19]. However, more and more studies have underlined the importance of pathogenic and saprophytic microorganisms and macrorganisms, such as earthworms, as a valuable tool for a variety of ecology-based applications, such as environmental bioindicators [20][21][22].…”
Section: Introductionmentioning
confidence: 99%